Rho Kinase (ROCK) Inhibitors in the Treatment of Glaucoma and Glaucoma Surgery: A Systematic Review of Early to Late Phase Clinical Trials - Jit Kai Tan; Peng Tee Khaw; Christin Henein (Pharmaceuticals)
Background/Objectives: Primary open-angle glaucoma (POAG) is an anterior optic neuropathy that can lead to irreversible vision loss if untreated. Prostaglandin analogues are the first-line treatment, but new drug classes, such as rho kinase (ROCK) inhibitors, are being explored. This review evaluates the efficacy and safety of ROCK inhibitors in treating POAG based on completed trials, comparing results with available natural history data and identifying areas for further research. Methods: A systematic database search was conducted in Ovid MEDLINE and Ovid Embase on 5 April 2022 using the following keywords: ‘glaucoma’, ‘rho kinase inhibitor’, ‘rho-kinase inhibitor’, ‘rock inhibitor’, ‘ripasudil’, ‘netarsudil’, and ‘fasudil’. Abstracts were screened for relevant studies and results summarized in tables. Results: The analysis of trials conducted for ROCK inhibitors reveals that they are a safe and efficacious drug to treat POAG, demonstrating non-inferiority to existing medical treatments. Comparison of data to natural history studies was inconclusive due to the lack of natural history studies and their limitations. The results showed ROCK inhibitors to be effective when combined with existing medical treatments. However, questions remain regarding the optimal dosage, patient selection, and cost-effectiveness. Outcome measures for future trials should be expanded to include additional methods of monitoring disease progression as well as patient quality-of-life. Conclusions: ROCK inhibitors have emerged with a favorable safety profile, efficaciously attenuating intraocular pressure. To elucidate their long-term therapeutic value and safety comprehensively, further independent, large-scale, prospective randomized controlled trials are warranted. Such studies are pivotal to augment our understanding of this emergent medication class.